Filsafat Ilmu dalam Perspektif Budaya Alam Minangkabau: Membangun Kearifan Lokal untuk Pengembangan Pengetahuan - Muhammad Aldi; Ahmad Barizi (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2025)
This article aims to examine the relationship between philosophy of science and Minangkabau natural culture in building local wisdom as the basis for knowledge development. This research focuses on how the values contained in Minangkabau culture can contribute to the formation of a scientific framework based on local wisdom. The method used is a qualitative approach with descriptive analysis of various literature sources, interviews with Minangkabau community leaders, and observations of cultural practices related to science in everyday life. The results showed that the philosophy of life in Minangkabau culture, such as “adat basandi syarak, syarak basandi kitabullah,” has a strong relevance in the development of knowledge based on the balance between rationality and spirituality. Local wisdom in Minangkabau culture, which includes values of togetherness, mutual cooperation, and respect for nature, can be applied in the process of developing science, which is more inclusive and holistic. In addition, the role of family and society in educating the younger generation about the importance of science and moral ethics is an important aspect in this context. The implication of this research is the importance of integration between Western philosophy of science and local cultural values in the education curriculum and science development in Indonesia. The contribution of this article is to provide a new perspective on how Minangkabau local wisdom can enrich and strengthen the structure of philosophy of science that not only focuses on theoretical aspects, but also involves social and spiritual dimensions in the development of sustainable knowledge Keywords: Philosophy of Science, Minangkabau Natural Culture, Local Wisdom, Knowledge